Concept analysis on healthy lifestyle in the context of primary health care (Research, Society and Development, 2021)
Objective: to analyze the concept of healthy lifestyle in the context of primary health care. Methodology: This is a concept analysis proposed by Walker and Avant, a model divided into eight steps, namely: concept selection; objectives of conceptual analysis; identification of possible uses of the concept; determination of defining attributes; identification of the model case; identification of antecedents and consequences; and definition of empirical references. Result: The concept of healthy lifestyle was selected in the context of PHC, later, an integrative review was carried out to identify the possible uses of the concept, namely: in UBS, in the community, in schools, in the family, at work, in the parks, gyms, countryside and gyms; the attributes: practice of physical activity, healthy eating, not smoking, not drinking alcohol, good night's sleep, performance of the multidisciplinary team, psychological balance, socioeconomic factors and health determinants; the antecedents: construction of Public Policies, assistance actions, health education, subjects' autonomy, preventive interventions; and the consequences: disease prevention, quality of life, well-being and longevity. Conclusion: Based on the research carried out, it was possible to develop a complete concept of healthy lifestyle in the context of PHC. It is noticed that in the literature the concept was approached in a fragmented and simplified way. Therefore, this work can be guided for the development of other stages of the process, strengthening the scientific body of nursing, supporting the development of technologies for the use of a healthy lifestyle in the context of PHC.